Exploring the self-efficacy and self-care-based stroke care model for risk factor modification in mild-to-moderate stroke patients - Rasyid, Al; Pemila, Uke; Aisah, Siti; Harris, Salim; Wiyarta, Elvan; Fisher, Marc (Frontiers in Neurology, 2023)
Context The worldwide burden of stroke is projected to grow unless proper stroke education is implemented. Information alone cannot promote patient self-efficacy and self-care and reduce risk factors. Aim This trial aimed to test self-efficacy and self-care-based stroke education (SSE) on changes in self-efficacy, self-care, and risk factor modification. Design, setting, and participants This study is a single-center, double-blinded, interventional, two-arm randomized controlled trial with a 1- and 3-month follow-up in Indonesia. Between January 2022 and October 2022, 120 patients were prospectively enrolled from Cipto Mangunkusumo National Hospital, Indonesia. Participants were assigned using a computer-generated random number list. Intervention SSE was given before discharge from the hospital. Primary outcome measure Self-care, self-efficacy, and stroke risk score was measured 1 month and 3 months after discharge. Secondary outcome measure Modified Rankin Scale, Barthel Index, and blood viscosity was measured at 1 month and 3 months after discharge. Results A total of 120 patients (intervention n = 60; standard care n = 60) were randomized. In the 1st month, the intervention group showed a more significant change in self-care (4.56 [95% CI: 0.57, 8.56]), self-efficacy (4.95 [95% CI: 0.84, 9.06]), and stroke risk (−2.33 [95% CI:−3.19, −1.47]) compared to the controlled group. In the 3rd month, the intervention group also showed a more significant change in self-care (19.28 [95% CI: 16.01, 22.56]), self-efficacy (19.95 [95% CI: 16.61, 23.28]), and stroke risk (−3.83 [95% CI: −4.65, −3.01]) compared to the controlled group. Conclusion SSE may boost self-care and self-efficacy, adjust risk factors, enhance functional outcomes, and decrease blood viscosity. Clinical trial registration ISRCTN11495822.